Related Structures in the Straight Sinus: An Endoscopic Anatomy and Histological Study - Ye, Yuanliang; Ding, Jiuyang; Huang, Shaoming; Wang, Qiujing (Frontiers in Neuroanatomy, 2020)
Some structure might be encountered with endovascular procedures within the straight sinus and aren't now readily seen on DSA. We investigated the morphological and histological characteristics of the straight sinus, chordae willisii (CW), and the junction between the great cerebral vein (GCV) and straight sinus. A total of cadaveric heads and 135 patients were analyzed with either anatomic dissection or neuroimaging. The morphological features of CW and the junction between GCV and straight sinus were analyzed by endoscope. The histology of the junction between GCV and straight sinus was evaluated under the microscope with staining for Elastic fiber, Masson's, and Immunohistochemistry. We found that fold, elevation, small bugle, or nodule and CWs were detected by endoscope in the straight sinus. The most common type of CWs was valve-like lamellae, which comprised 40.46% of all CWs. Three different types of junctions between GCV and straight sinus were identified: type 1 has folds in the GCV and elevation on the floor of straight sinus; type 2 has folds and a small bugle; type 3 presents with an intraluminal nodule located at the opening of the GCV. Compared to arachnoid granulation, the nodule consists of smooth muscle fibers and higher rate of elastic fibers. Understanding the detailed anatomy of the straight sinus may help surgeons to avoid procedural difficulties and to achieve higher success rate.